2009
DOI: 10.1088/1741-2560/6/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a wide-field retinal prosthesis

Abstract: The purpose of this article is to present a wide field electrode array that may increase the field of vision in patients implanted with a retinal prosthesis. Mobility is often impaired in patients with low vision, particularly in those with peripheral visual loss. Studies on low vision patients as well as simulation studies on normally sighted individuals have indicated a strong correlation between the visual field and mobility. In addition, it has been shown that increased visual field is associated with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…The size range has been chosen on the basis of the device requirement for larger electrodes of greater than 200 µm diameter to safely stimulate potentially distal neurons (25) in comparison with cortical prostheses where microelectrodes usually penetrate into and are in contact with the target tissue. However, the visual field imparted by a vision prosthesis is directly related to the size of the stimulated area of the retina, and hence, the overall dimensions of the electrode array, (26) which are determined from both the electrode diameter and packing limitations of the fabrication process. A study by Onnela et al has suggested that either novel electrode materials or surface treatment methods will be required to meet the charge injection needs of a high resolution of vision prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The size range has been chosen on the basis of the device requirement for larger electrodes of greater than 200 µm diameter to safely stimulate potentially distal neurons (25) in comparison with cortical prostheses where microelectrodes usually penetrate into and are in contact with the target tissue. However, the visual field imparted by a vision prosthesis is directly related to the size of the stimulated area of the retina, and hence, the overall dimensions of the electrode array, (26) which are determined from both the electrode diameter and packing limitations of the fabrication process. A study by Onnela et al has suggested that either novel electrode materials or surface treatment methods will be required to meet the charge injection needs of a high resolution of vision prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ameri et al describes a foldable array that can be inserted through a small sclerotomy (eye wall incision), then expanded once in the eye. [52] This approach allows 1 cm wide array, thus 45-50 degrees of visual angle. Subsequent development of this idea has demonstrated long-term implantation of these arrays into animal eyes.…”
Section: Engineering Researchmentioning
confidence: 99%
“…Other advantages for this disease as an initial target of iPS cell therapies are that surgical procedures for grafting are well studied [75], considerable effort has gone into developing prostheses, which helps inform technical approaches to the eye and assays for following patients [76], and there is recent industry interest in iPS-derived RPE cells [77]. In addition, long-term follow-up of animals that received human ESC-derived RPE revealed no major safety issues [78].…”
Section: Future Perspectivementioning
confidence: 99%